2016
DOI: 10.1177/1524838016650189
|View full text |Cite
|
Sign up to set email alerts
|

Technology-Facilitated Sexual Violence: A Literature Review of Empirical Research

Abstract: Technology-facilitated sexual violence (TFSV) refers to a range of behaviors where digital technologies are used to facilitate both virtual and face-to-face sexually based harms. Such behaviors include online sexual harassment, gender- and sexuality-based harassment, cyberstalking, image-based sexual exploitation, and the use of a carriage service to coerce a victim into an unwanted sexual act. This article reviews the current state of knowledge on these different dimensions, drawing on existing empirical stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
247
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 333 publications
(267 citation statements)
references
References 63 publications
(121 reference statements)
9
247
0
11
Order By: Relevance
“…Consistent with developments in gender-based violence generally (see Henry and Powell 2016), victims are also reporting abuse mediated online. Perpetrators include intimate partners, parents, siblings, relations, in-laws and other non-family members of the community.…”
Section: Literature Reviewmentioning
confidence: 53%
“…Consistent with developments in gender-based violence generally (see Henry and Powell 2016), victims are also reporting abuse mediated online. Perpetrators include intimate partners, parents, siblings, relations, in-laws and other non-family members of the community.…”
Section: Literature Reviewmentioning
confidence: 53%
“…Examples of sexual harassment in online video games include sexist jokes, sexist insults, unwanted sexual advances, rape jokes, and comments about female players’ appearances (Fox & Tang, ). Sexual harassment is perpetrated most often by men targeting women in both offline and online contexts (Henry & Powell, ; Pina et al, ). Field experiments in online video games where researchers interacted with other anonymous players using prerecorded neutral messages revealed that these players reacted depending on the voice's gender.…”
Section: Online Sexual Harassmentmentioning
confidence: 99%
“…However, this study is not without limitations: Tang and Fox () relied on a self‐selected sample, a specific game of choice and the US‐context. Also, the study was limited to men's perpetration in video games as past studies indicate that men perpetuate more sexual harassment than women across contexts; henceforth it is not known how often women perpetuate these behaviors (Henry & Powell, ; Pina, Gannon, & Saunders, ).…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, human interaction in a virtual environment resembles relationships in the real world, and old forms of harassment, including sexual harassment and harassment on the grounds of sex, have adapted to this new habitat, in the form of new violence [9,10]. As a result, we are now getting used to concepts such as cyberstalking, doxing, phishing, grooming, or sextortion.…”
Section: Featured Application: a Complete Review Of Information And Cmentioning
confidence: 99%
“…In the early 1990s, Haraway [7] anticipated the social changes and the effect, especially in gender issues, that would accompany ICT. It is important to bear in mind that ICT has changed the way we interact socially in issues as important as job seeking, health promotion, commerce, work, and every kind of human relations [8].In this sense, human interaction in a virtual environment resembles relationships in the real world, and old forms of harassment, including sexual harassment and harassment on the grounds of sex, have adapted to this new habitat, in the form of new violence [9,10]. As a result, we are now getting used to concepts such as cyberstalking, doxing, phishing, grooming, or sextortion.…”
mentioning
confidence: 99%